2010
DOI: 10.1007/s11524-010-9487-8
|View full text |Cite
|
Sign up to set email alerts
|

Congruence between Urban Adolescent and Caregiver Responses to Questions about the Adolescent’s Asthma

Abstract: In clinical and research settings, it is increasingly acknowledged that adolescents may be better positioned than their caregivers to provide information in regard to their own health status, including information related to asthma. Very little is known, however, about the congruence between adolescent and caregiver responses to questions about asthma beyond reports of symptoms. We analyzed data for 215 urban, primarily African-American adolescent-caregiver pairs. Adolescents and caregiver reports concerning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…One limitation of this study may be its reliance on teen self-report for all outcome measures. Objective data to validate outcomes were not available due to the community-based recruitment and assessment strategy in the SB-ACT study; however, teens have been shown to reliably report on their asthma and healthcare use [39]. Social desirability bias may explain associations between readiness for talking with providers, and other medication belief scales [40].…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of this study may be its reliance on teen self-report for all outcome measures. Objective data to validate outcomes were not available due to the community-based recruitment and assessment strategy in the SB-ACT study; however, teens have been shown to reliably report on their asthma and healthcare use [39]. Social desirability bias may explain associations between readiness for talking with providers, and other medication belief scales [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence suggests that youth reports of physical health are both reliable and valid, particularly after the age of 8 years, and predict health care use more than parent reports (57,58). For adolescents who have some autonomy from parents and may not consistently inform parents of fluctuations in symptoms, adolescent-reported information is important for symptom-based conditions (59). Nonetheless, these findings warrant replication in samples using medical records, claims data, or physician report.…”
Section: Discussionmentioning
confidence: 99%
“…The parent cohort rated their child's skill levels lower than their child's self-report for all sections and overall. The level of agreement did not improve with age, as has been found in children with asthma (41). Although the underestimation of children's selfmanagement skills by parents has been mirrored in other pediatric disease groups (32,36,42), comparative data specific to children with IBD are scant.…”
Section: Discussionmentioning
confidence: 84%